BIOCOMPATIBILITY OF AZITROMICYN ON CONNECTIVE TISSUE - Kurnia, Shafira (Institute of Topical Disease Universitas Airlangga, 2011)
Background: periodontal disease is commonly caused by bacteria, especially actinomyces actinomycetemcomitans and porphyromonas gingivalis have an abilty enter epithelial cells objectives: to investigate systemic azithromycin as the antibiotic of choice for periodontal disease based on biocomptability test in connective tissue. Material and Methods: BHK 21 cell lines were exposed to 0.025%, 0.050%, 0.075%, and 0.1% azithromycin solution for seven times. Samples were put in incubator for 24 hours. Result: Azitrromycin 0.050%-0.1% showed significant difference between life cells percentage and control, however, azithromycin 0.025% revealed insignificant difference with control. Conclusion: 0.025% azithromycin was considered biocompatible with connective tissue and 0.050% was not.